Pendekatan antropologi sebagai penyeimbang model perhitungan jejak ekologis di Desa Wisata - Anna Pudianti; Vincentia Reni Vitasurya (ARTEKS : Jurnal Teknik Arsitektur, 2019)
Anthropology approach as a balancer of ecological footprint calculation models in Tourism Village Tourism is currently experiencing a shift from mass tourism to special interest tourism focusing on nature and culture. In the context of preservation, rural tourism experiences a sharp pros and cons as supporting or inhibiting aspects of conservation. This study uses one of the environmental conservation evaluation instruments with an ecological footprint calculation model that analyzes quantitatively the aspects of transportation, water use, clothing use, recreation, food, garbage and shelter. Given the limitations of the ecological trace calculator model to be applied in tourism villages, the implementation of the model needs to be modified using the anthropological approach. The research method used is action research participation by measuring the impact of tourism activities in rural areas using simple indicators of ecological footprint calculations and equipped with in-depth interviews to explore aspects of collective behavior as the focus of the anthropological approach studied. Case studies include three villages in the Yogyakarta region, namely Pentingsari in Sleman regency, Lopati in Bantul and Kalibiru districts in Kulonprogo district. The results obtained are recommendations for anthropological approaches to evaluate the ecological footprint results so that they are more appropriate if they are used as an environmental conservation action plan in a tourist village with the emphasis on forming awareness of living with nature. © 2019 Anna Pudianti, Vincentia Reni Vitasurya